Spanish Colonial Tucson A Demographic History - Dobyns, Henry F. (University of Arizona Press, 1976)
"[Dobyns] has written a fascinating account of the ethnic development of early Tucson. Using a variety of methods and sources, he reveals how Spaniards, mestizos from New Spain, and Native Americans from many tribes laid the ethnic foundations for the modern city. The book also provides much insight into the general history of Spanish colonial society as it evolved in the Tucson area to 1821. . . . Dobyns, utilizing previously unpublished primary sources, allows the early inhabitants of the Tucson area to speak for themselves, and their comments add much to a very colorful and exciting but often grim story. . . . And his penetrating look at the ethnic development of early Tucson should attract attention from anyone interested in a better understanding of how the nation as a whole achieved its multi-cultural character." -The Journal of American History